COMPETITION BETWEEN THREE LICHEN SPECIES USING A FACTORIAL EXPERIMENTAL DESIGN - Armstrong, R A (The New phytologist, 1986)
Competition between three foliose lichens common on slate rock in south Gwynedd, Wales was studied in the field using a factorial experimental design. The lichens were grown as fragments glued to pieces of slate in two- and three-species mixtures. In the two-species mixtures, Parmelia conspersa (Ehrh. ex Ach.) Ach. outcompeted Parmelia glabratula ssp. fuliginosa (Fr. ex Duby) Laund. strongly and Physcia orbicularis (Neck.) Poetsch less strongly, while P. orbicularis outcompeted P. glabratula weakly. Significant two-factor interactions indicated that the results from the three-species mixture could not be predicted from the two-species mixtures. Parmelia glabratula and P. orbicularis grew better in the presence of two competitors than one. This result suggests that the three species may co-occur on well-lit rock surfaces at the site